From the Morals of Sacrifi ce to the Consciousness of Precariousness. A Qualitative Analysis of Discourses regarding the Evolution of the Crisis in Spain - Alonso, Luis Enrique; Fernández Rodríguez, Carlos Jesús; Ibáñez Rojo, Rafael (Política y Sociedad, 2016)
The long economic crisis affecting Spain has brought major social consequences. The increasing social divide inside the country is the most discussed topic among academics, mass media and members of the political spectrum, being the result of growing economic inequalities due to high unemployment and harsh adjustment policies of public spending. However, and beyond economic issues the crisis is taking its toll very deeply in the social imaginary of the country, bringing further refl ections about the reasons and consequences of the crisis, both in short and long term. The aim of this paper is to explore the social perceptions of the Spanish citizens about the crisis, focusing on aspects such as how Spaniards perceive the consumption of public goods and services, in a scenario of a clear hegemony of austerity as the only anti-recession remedy. To do so, a discourse analysis on focus groups transcriptions (collected during a qualitative research conducted in 2014) will be carried out. The results show a huge pessimism about the future of the welfare state and the Spanish middle class itself, whose frustration may lead to future waves of social unrest.
Keywords: imaginary; crisis; middle class; austerity; discourse analysis